Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel blaKLUC Variant With Reduced β-Lactam Resistance From an IncA/C Group Plasmid in a Clinical Klebsiella pneumoniae Isolate

Abstract: Similar to other CTX-M family enzymes, KLUC is a recently identified and emerging determinant of cefotaxime resistance that has been recovered from at least three Enterobacteriaceae species, including Kluyvera cryocrescens, Escherichia coli, and Enterobacter cloacae. Whether this extended-spectrum β-lactamase (ESBL) has been disseminated among commonly isolated Enterobacteriaceae is worthy of further investigation. In this study, we screened 739 nosocomial Enterobacteriaceae isolates (240 Klebsiella pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Another type of ESBL gene is transferred to K. pneumoniae through horizontal gene transfer (HGT), bla OXA type ESBLs included [ 41 ] and scarce genes bla GES and bla SFO [ 42 ], or bla PER, bla TLA, and bla VEB [ 43 ] and bla KLUC-5 [ 44 ]. In addition, β-lactamase genes that are tolerant to inhibitors have emerged, and they encode enzymes that are partially inhibited by tazobactam and clavulanic acid [ 75 ].…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Another type of ESBL gene is transferred to K. pneumoniae through horizontal gene transfer (HGT), bla OXA type ESBLs included [ 41 ] and scarce genes bla GES and bla SFO [ 42 ], or bla PER, bla TLA, and bla VEB [ 43 ] and bla KLUC-5 [ 44 ]. In addition, β-lactamase genes that are tolerant to inhibitors have emerged, and they encode enzymes that are partially inhibited by tazobactam and clavulanic acid [ 75 ].…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The spread of CTX-M is dependent upon its mobility. The mobilization of bla CTX-M genes from their original chromosomal position in Kluyvera species has been facilitated by mobile genetic elements, such as ISEcp1 or ISCR1, and their later incorporation in mobilizable genetic platforms, including class 1 integrons, plasmids and/or transposons [64]. The insertion sequence ISEcp1 provides a high-level expression promoter for the bla CTX-M gene and is positioned upstream of bla CTX-M genes from group CTX-M-1, -2, -9 and -25 enzymes [58,65].…”
Section: Dissemination Of Ctx-m and Its Implicationsmentioning
confidence: 99%
“…The evolution of resistance over the last 20 years, with the spread of ESBL-PE, demonstrates the important role of the environment in this phenomenon. In fact, it is well demonstrated that the transfer of resistant genes through plasmid mobilization from an environmental bacterial species, Kluyvera sp , was responsible for the spread of ESBL-PE on a worldwide scale [ 21 ].…”
Section: Antibiotic Resistance Is An Ancient Phenomenon Enhanced By Antibiotic Prescriptionsmentioning
confidence: 99%